Initial approaches to develop the business capacity of Bondo Bakery, a homemade bakery producer in Padang - Aronal Arief Putra; Elfi Rahmi; Vitania Yulia; Afriani Sandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
A community engagement initiative was conducted with Bondo Bakery, a local homemade bakery producer in Padang. The goal was to assess the bakery's current conditions and explore ways to enhance its business capacity. Activities included visits to the processing room, focus group discussions, product development for premium variants, training for home industry food production, and technical support for MSME business permit registration. These efforts aimed to establish foundational steps for identifying necessary improvements related to the processing room, expanding the range of bakery products to include options enriched with animal products, mapping the competitive landscape to inform strategic planning, and enhancing knowledge of food production practices—including good manufacturing practices (GMP), food quality and safety, and relevant regulations in the food sector. Furthermore, assistance in acquiring a business permit was provided. In conclusion, these collaborative actions have positively contributed to strengthening the business capacity of the enterprise.